Between the Fetter and the Unveiling: Ibn al-Jawzī's Moral Rationalism in Dialogue with Classical Sufi Epistemology - Muhammad Imran Saleem Channar (Academica: Journal of Multidisciplinary Studies, 2025)
Objective: This study reconstructs a comprehensive philosophical theory of intellect (ʿaql) in the thought of Ibn al-Jawzī (d. 597/1201) in order to examine his distinctive articulation of moral rationalism. Method: Drawing on systematic textual analysis of his major works, Kitāb al-Adhkiyāʾ, Talbīs Iblīs, Dhamm al-hawā, al-Ṭibb al-rūḥānī, Ṣayd al-khāṭir, and Minhāj al-qāṣidīn. Result: The article demonstrates that Ibn al-Jawzī develops a coherent philosophical anthropology in which the intellect occupies an architectonic position. Within this framework, the intellect functions as the governing faculty over passion (hawā), the primary safeguard against satanic epistemological deception (talbīs), and the foundation of ethical praxis and moral self-discipline. This model of intellect-centered moral rationalism is then situated within a sustained hermeneutical dialogue with classical Sufi epistemologies that privilege the heart (qalb), as represented by al-Junayd al-Baghdādī, al-Ḥakīm al-Tirmidhī, Abū Ṭālib al-Makkī, al-Sarrāj, al-Ghazālī, and Ibn al-ʿArabī. The comparative analysis reveals fundamental epistemological divergences between Ibn al-Jawzī’s rationalist ethical framework and the experiential–intuitive orientation of classical Sufism. Conclusion: By foregrounding Ibn al-Jawzī as a systematic moral rationalist, this study contributes to contemporary debates in virtue epistemology and Islamic psychology, offering a refined conceptual lens for understanding reason, ethics, and moral formation in classical Islamic thought.